Interest Rate Pass-Through: Empirical Study Towards Monetary Policy Transmission Effectiveness in Indonesia - Heni Hasanah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This research aims to measure the effectiveness of monetary policy transmission, especially through the interest rate channel. The analysis was conducted on the first stage of its transmission, namely Interest Rate Pass-through (IRPT). IRPT refers to condition in which retail interest rate (both deposit and lending rate) responds to changes in policy rate of central bank. IRPT was measured using Error Correction Model (ECM) for time series data in the period of January 2010 - December 2015. The results of this study indicated that degree of long term and short term IRPT is incomplete for deposit and lending rate. In addition, IRPT for deposit rate is higher than lending rate, but the adjustment process of lending rate faster than deposit rate. Finally, model that include other variables (macroeconomic and internal banking indicator) generate long term IRPT which is smaller than the standard model. This results implies that the Central Bank, the FSA, and government needs to pay attention to the stability of the other variables that may interfere or reduce the effectiveness of monetary policy through the interest channel. JEL Classification: E42, E43, E52Keywords: Deposit rate, ECM, IRPT, Lending Rate, Policy Rate